Układ sił w procesie decyzyjnym Rady Unii Europejskiej - wpływ rozszerzenia Unii - Mayer, Eric C. (Decision Power in the European Council - the Impact of EU Enlargment, 2005)
The Council of the European Union plays a prominent role in the decision making process of the European Community. Although the European Parliament recently gained legislative strenght by the extended application of the co-decision procedure, the Council remains the most influential body within the Community's institutional system. Accorging to the prescriptions of the act's legal base Council decisions are adopted either unanimously or by qualified majority. While power in unanimous decisions is distributed equally, the individual member state's influence diverges in qualified majority voting have always been an intensively disputed issue, the recently resurfaced in the debates oreceding the adoption of the Nice Treaty. This paper attempts to elucidate the effects of the Nice Treaty's new regulations on qualified majority voting in the Council of the European Union by applying power measure indices. The analysis will focus on two aspects: the impact of new voting weights and the required population quota in todaz's 15 member union and the consequences of enlargement on voting power in the future. After briefly reviewing problems and methods of measuring power in section two, the Community's legislative decision procedures will be described in section three. Then section four will present the contents of the Nice Treaty with respect to voting in the Council. Finally the analysis of voting power is carried out in section five.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 169-193